Intraosseous infusion of the distal phalanx compared to systemic intravenous infusion for marimastat delivery to equine lamellar tissue. Issue 3 (September 2015) - Underwood, Claire; Collins, Simon N.; van Eps, Andrew W.; Mills, Paul C.; Allavena, Rachel E.; Bailey, Simon R.; Medina Torres, Carlos E.; Meizler, Alon; Pollitt, Christopher C.
Highlights Ultrafiltration was used to collect lamellar interstitial fluid for pharmacokinetic analyses. IOIDP with marimastat results in similar lamellar marimastat concentrations to systemic intravenous constant rate infusion. Further refinement of the IOIDP technique is necessary if it is to be useful for local lamellar drug delivery.